Health information technology acceptance model : a study on diabetic patients' perspective in Nigeria - Isma'eel, Ahmad Barroon (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2016)
Health Information Technology (HIT) systems such as Electronic Health Record (EHR), Computerized Physician Order Entry (CPOE) and Clinical Decision Support System (CDSS) are reported to have potential benefits that include improving physicians' performance, patients' outcome and reducing healthcare cost among others. The benefits that patients in low and middle economic settings would derive from HIT include reduction in healthcare cost, improving quality of care and wider healthcare delivery coverage. Nevertheless, the acceptance of such technologies in developing countries particularly Nigeria is quite low. There are studies that report factors influencing technology acceptance by physicians and nurses, but empirical studies on patients' acceptance of HIT in Nigeria are lacking. This research aimed at filling this gap by identifying and examining factors affecting diabetic patients' acceptance of HIT in Nigeria. The study was conducted in two phases which was guided by the mixed method design methodology. Factors that affect the acceptance of HIT were examined in phase I, which is the qualitative phase. Data were collected from semi-structured interview with 28 participants and were analysed using NVIVO. Findings from phase I were used in conjunction with previous literature to build the instrument for collecting data in phase II, which is the quantitative phase. The instrument was based on Technology Acceptance Model (TAM) which was the theoretical framework for the study. In this second phase, 600 questionnaires were administered to diabetic patients from two hospitals in Kano, Nigeria out of which 540 completed questionnaires were received. The quantitative data were analysed using Statistical Package for the Social Sciences (SPSS) and Analysis of Moment Structures (AMOS) software. Confirmatory Factor Analysis (CFA) evaluated the model and later the hypotheses were tested using path analysis. Six factors were identified and evaluated in this study. They are perceived usefulness, perceived ease of use, perceived output quality, perceived cost-effectiveness, attitude, and intention. The postulated relationship between these factors were all supported except the path between perceived cost-effectiveness and attitude. These factors and their relationships formed the basis of our extended TAM model called Health Information Technology Acceptance Model (HTAM). This study significantly contributes to HIT field by exploring factors that affect HIT adoption by patients in Nigeria, and validate a model for the assessment of the factors in the context of diabetes management. The findings of this study provide some implications for government, healthcare providers, and other policy makers on the assessment of HIT acceptance in Nigeria in order to increase the adoption rate; and by implication the delivery of healthcare will be improved. This involves creating awareness about the benefits of HIT in diabetes management. The findings also suggested the use of a simple and robust design, good design features, and cost-effective technology when developing HIT systems.